2020
DOI: 10.1177/2045894020925762
|View full text |Cite
|
Sign up to set email alerts
|

Endurance exercise training in pulmonary hypertension increases skeletal muscle electron transport chain supercomplex assembly

Abstract: Pulmonary hypertension is associated with pronounced exercise intolerance (decreased V ċ O2 max) that can significantly impact quality of life. The cause of exercise intolerance in pulmonary hypertension remains unclear. Mitochondrial supercomplexes are large respiratory assemblies of individual electron transport chain complexes which can promote more efficient respiration. In this study, we examined pulmonary hypertension and exercise-induced changes in skeletal muscle electron transport chain protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…However, the absence of paired control subjects, the lack of measurements of the ATP cost of contraction or the limited details regarding the exercise done to measure phosphocreatine recovery time preclude confident conclusions to be made from that study. Interestingly, MCCULLOUGH et al [145] demonstrated plasticity in mitochondrial function after endurance exercise training in Sugen/hypoxia PAH rat model, especially for mitochondrial complex I and III.…”
Section: Skeletal Muscle Mitochondrial Function Abnormalitiesmentioning
confidence: 99%
“…However, the absence of paired control subjects, the lack of measurements of the ATP cost of contraction or the limited details regarding the exercise done to measure phosphocreatine recovery time preclude confident conclusions to be made from that study. Interestingly, MCCULLOUGH et al [145] demonstrated plasticity in mitochondrial function after endurance exercise training in Sugen/hypoxia PAH rat model, especially for mitochondrial complex I and III.…”
Section: Skeletal Muscle Mitochondrial Function Abnormalitiesmentioning
confidence: 99%
“…Functional impairment can manifest as reduced muscle strength, decreased muscular endurance, impaired oxygenation in the microcirculation, reduced type I fiber tension, and sarcomeric dysfunction ( 6 , 8 , 9 , 44 , 45 ). Molecular abnormalities have been described including reduced oxidative capacity, increased protein degradation and decreased protein synthesis, impaired angiogenesis, and impaired mitochondrial function ( 11 , 46 , 47 ). The spectrum of muscular abnormalities in children with PH is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, PAH decreases exercise tolerance. On the other hand, it was verified that aerobic physical exercise increases the maximum consumption of oxygen ( McCullough et al, 2020 ), as well as increases the cross-sectional area of the skeletal muscle, which improves exercise tolerance ( Moreira-Gonçalves et al, 2015a ).…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…The study by Kue et al (2017) reported that the soleus muscle of animals with PAH showed a reduction in the expression of the coactivator-1 alpha of the receptor activated by gamma peroxisome proliferators (PGC1α) and mitochondrial DNA (mtDNA), without alteration in OPA1, thus, impairing mitochondrial biogenesis. Additionally, McCullough et al ( McCullough et al, 2020 ) demonstrated that PAH induced by Sugen/Hypoxia promoted negative changes in the expression of electron transport chain supercomplexes in the gastrocnemius of rats. Mitochondrial supercomplexes are dynamic sets of individual complexes in the electron transport chain that can lead to more efficient respiration ( Genova and Lenaz, 2014 ).…”
Section: Pulmonary Arterial Hypertension and Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation